2020
DOI: 10.1016/j.kint.2020.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and volume management in dialysis: conclusions from a Kidney Disease: Improving Global Outcomes (KDIGO) Controversies Conference

Abstract: Research recommendations within each topic area are listed in order of priority, stratified by modality type.JE Flythe et al.: BP and volume control in dialysis: a KDIGO conference report

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
182
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(186 citation statements)
references
References 175 publications
2
182
0
2
Order By: Relevance
“…However, strong evidence for selection of [Na + ] D is lacking and there was no consensus in the recent KDOQI guideline. 1 Most studies have focused on osmotically active sodium. However, this concept of sodium homeostasis has been challenged after a long-term sodium balance study in humans in a protracted space flight simulation.…”
mentioning
confidence: 99%
“…However, strong evidence for selection of [Na + ] D is lacking and there was no consensus in the recent KDOQI guideline. 1 Most studies have focused on osmotically active sodium. However, this concept of sodium homeostasis has been challenged after a long-term sodium balance study in humans in a protracted space flight simulation.…”
mentioning
confidence: 99%
“…On the other hand, Abdominal aorta is a susceptible site for atherosclerosis and calci cation, so the presence of AAC is related to the occurrence of CV disease and death in patients [32][33][34] . Therefore, both the 2009 Kidney Disease: Improving Global Outcomes (KDIGO) guideline and the 2017 KDIGO guideline update suggested that in patients with CKD G3a-G5D, a lateral abdominal X-ray can be used to assess the presence of vascular calci cation by estimating the calci cation of abdominal aorta [35] .…”
Section: Discussionmentioning
confidence: 99%
“…Tekanan darah pasien dialisis berdampak pada gejala pasien, kualitas hidup, dan komplikasi kardiovaskular [13]. Hipertensi intradialitik pada pasien hemodialisis rutin dikaitkan dengan peningkatan mortalitas .…”
Section: Pendahuluanunclassified